1991
DOI: 10.3109/09593989109106961
|View full text |Cite
|
Sign up to set email alerts
|

Grip strength as a function of age, height, body weight and Quetelet index

Abstract: The primary aim of this study was to determine the viability of using physical characteristic parameters to predict grip strength. We measured the weight, height, Quetelet index (weight/height') and grip strength of 960 subjects (480 males and 480 females), ranging in age from 7 to 84 years. We analysed our data using linear-, multiple-and stepwise-regression models. We found that grip strength is positively related to: (1) age up to the third decade of life, and thereafter grip strength is inversely related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 11 publications
1
21
1
Order By: Relevance
“…; Bechtol, 1954;Schmidt and Toews, 1970;Agnew and Maas, 1982;Fraser and Benten, 1983;Mathiowetz et al, 1985;Hinson and Gench, 1989;Balogun et al, 1991;Crosby and Wehbe, 1994;Harth and Vetter, 1994;Josty et al, 1997;Fraser et al, 1999;Xiao et al, 2005;Bohannon et al, 2006;Anakwe et al, 2007;Wu et al, 2009;Werle et al, 2009). Several of these studies are described in more detail below.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…; Bechtol, 1954;Schmidt and Toews, 1970;Agnew and Maas, 1982;Fraser and Benten, 1983;Mathiowetz et al, 1985;Hinson and Gench, 1989;Balogun et al, 1991;Crosby and Wehbe, 1994;Harth and Vetter, 1994;Josty et al, 1997;Fraser et al, 1999;Xiao et al, 2005;Bohannon et al, 2006;Anakwe et al, 2007;Wu et al, 2009;Werle et al, 2009). Several of these studies are described in more detail below.…”
Section: Introductionmentioning
confidence: 91%
“…The study by Balogun et al (1991) with 960 volunteers (480 males and 480 females; 7e84 years) from Nigeria reported that static grip strength is positively related to both body weight and height at all ages, BMI, and age up to the third decade of life, and thereafter grip strength is inversely related to age. Crosby and Wehbe (1994) studied 214 participants and found that height, weight, gender, hand dominance and hobby demands were predictive of grip strength.…”
Section: Introductionmentioning
confidence: 98%
“…However, in the study of Kellor et al (1971), the subjects were permitted to position their arms as they preferred, with elbows either flexed or extended; the reason for this was not clearly defined. Similarly, in a study referred to by Balogun et al (1991), in which the effect of elbow position on grip strength measurements was assessed, it was reported that the maximum grip strength was obtained with the subject in standing position and the elbow joint in full extension.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The report also indicated that grip strength was positively related to both body weight and height for all ages, and the Quetelet index (a measure of adiposity) during the first two decades of life. Balogun et al (1991) finally recommended that grip strength normative data should be based on both weight and age rather than age alone. Fraser and Benten (1983) also reported that in a population of 60 British men aged 20-79 years, a deterioration of grip strength with age was noted, being most marked over 50 years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies reported that women exerted only 56~70% of men's grip force (Pheasant and Scriven, 1983;Härkönen et al, 1993;Talsania and Kozin, 1998;Kong and Lowe, 2005). The difference in grip force according to gender is caused by differences in the muscles' physiological cross-sectional area (Miller et al, 1993), the size of the hand (Desrosiers et al, 1995), and the height and weight of men and women (Balogun et al, 1991;Hanten et al, 1999). In particular, the difference by gender in muscle strength in the upper limbs compared with lower limbs was more obvious based on previous studies (Levine et al, 1984;Heyward et al, 1986).…”
Section: Grip Forcementioning
confidence: 99%